THE IMPACT OF HEADMASTER’S LEADERSHIP PRACTICE ON THE FORMATION OF A PROFESSIONAL LEARNING COMMUNITY AT SCHOOL - Geske, Andrejs; Rečs, Normunds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the context of general education content reform initiated in Latvia, which also provides change of teaching approach, the issue of the role of headmaster has raised. The introduction and implementation of competence approach requires strengthening and development of cooperation between teachers in professional learning communities (PLCs) at school, in order to address didactic issues, regularly analyze pupils` learning outcomes and find best ways to increase the learning outcomes of each pupil, and give an opportunity for teachers to improve their teaching by sharing good pedagogical practice. The change of teaching approach prompts a revision of school management practices as well. In order for the school to grow, there is a need for a headmaster-leader, not just a headmaster-manager and he should focus on the leadership of the teaching process by improving teaching and learning and ensuring conditions for effective learning at school. The main goal of the research is to find out to what extent the headmaster`s pedagogical leadership practice has an impact on the PLCs formation at school. The article discusses theories of the concept of headmaster as pedagogical leader and PLCs, and analyzes the results of 489 teacher survey.